l log(85)

Evaluate the following logarithmic expression

log(85)

Evaluate log(85)

You didn't enter a base

We'll do bases e and 2-10

Evaluate loge(85) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = e and x = 85, we have:

loge(85)  =  Ln(85)
  Ln(e)

Ln(e) = 1

loge(85) = 4.4426512564903

Evaluate log2(85) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 2 and x = 85, we have:

log2(85)  =  Ln(85)
  Ln(2)

log2(85) = 6.4093909361377

Evaluate log3(85) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 3 and x = 85, we have:

log3(85)  =  Ln(85)
  Ln(3)

log3(85) = 4.0438754438805

Evaluate log4(85) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 4 and x = 85, we have:

log4(85)  =  Ln(85)
  Ln(4)

log4(85) = 3.2046954680689

Evaluate log5(85) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 5 and x = 85, we have:

log5(85)  =  Ln(85)
  Ln(5)

log5(85) = 2.7603744277226

Evaluate log6(85) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 6 and x = 85, we have:

log6(85)  =  Ln(85)
  Ln(6)

log6(85) = 2.4794908763085

Evaluate log7(85) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 7 and x = 85, we have:

log7(85)  =  Ln(85)
  Ln(7)

log7(85) = 2.2830711164373

Evaluate log8(85) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 8 and x = 85, we have:

log8(85)  =  Ln(85)
  Ln(8)

log8(85) = 2.1364636453792

Evaluate log9(85) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 9 and x = 85, we have:

log9(85)  =  Ln(85)
  Ln(9)

log9(85) = 2.0219377219402

Evaluate log10(85) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 10 and x = 85, we have:

log10(85)  =  Ln(85)
  Ln(10)

log10(85) = 1.9294189257143

Final Answer


loge(85) = 4.4426512564903
log2(85) = 6.4093909361377
log3(85) = 4.0438754438805
log4(85) = 3.2046954680689
log5(85) = 2.7603744277226
log6(85) = 2.4794908763085
log7(85) = 2.2830711164373
log8(85) = 2.1364636453792
log9(85) = 2.0219377219402
log10(85) = 1.9294189257143